Targeting the gut microbial metabolic pathway with small molecules decreases uremic toxin production - Yingyi Wang (Gut Microbes, 2020)
Uremic toxins are a class of toxins that accumulate in patients with chronic kidney disease (CKD). Indoxyl sulfate (IS), a typical uremic toxin, is not efficiently removed by hemodialysis. Modulation of IS production in the gut microbiota may be a promising strategy for decreasing IS concentration, thus, delaying CKD progression. In the present study, we identified isoquercitrin (ISO) as a natural product that can perturb microbiota-mediated indole production without directly inhibiting the growth of microbes or the indole-synthesizing enzyme TnaA. ISO inhibits the establishment of H proton potential by regulating the gut bacteria electron transport chain, thereby inhibiting the transport of tryptophan and further reducing indole biosynthesis. This non-microbiocidal mechanism may enable ISO to be used as a therapeutic tool, specifically against pathologies triggered by the accumulation of the microbial-produced toxin IS, as in CKD. Herein, we have shown that it is possible to inhibit gut microbial indole production using natural components. Therefore, targeting the uremic toxin metabolic pathway in gut bacteria may be a promising strategy to control host uremic toxin production.